2015
DOI: 10.1007/s11748-015-0550-y
|View full text |Cite
|
Sign up to set email alerts
|

The long-term outcomes of physiologic repair for ccTGA (congenitally corrected transposition of the great arteries)

Abstract: An analysis of the results of physiologic repair for ccTGA showed that the long-term outcome was overall favorable. To maintain RV function, early TVR may be a reasonable option, even in the management of patients during childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This improved longer term survival outcome over physiological repair needs to be weighed over the apparent short-term safety of only correcting associated abnormalities in a physiologic repair strategy[ 34 ]. However, the surgical mortality in physiologic repair population is also not negligible, being reported at 3% in operations done after 1986 in a Mayo Clinic series (16% overall) and 6.7% in the Dutch series by Bogers et al[ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This improved longer term survival outcome over physiological repair needs to be weighed over the apparent short-term safety of only correcting associated abnormalities in a physiologic repair strategy[ 34 ]. However, the surgical mortality in physiologic repair population is also not negligible, being reported at 3% in operations done after 1986 in a Mayo Clinic series (16% overall) and 6.7% in the Dutch series by Bogers et al[ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among this group, overall survival was 82% at 10 years. 16 Similarly, Hirose et al, 17 Lim et al, 18 and Dobson et al 19 reported excellent longterm survival (upward of 90%) among ccTGA patients undergoing physiologic repair, though nearly half required tricuspid valve intervention. 17 Although we recognize the uncertain fate of the systemic RV among the totality of anatomic subtypes in the spectrum of ccTGA, and the potential selection bias inherent in noninception cohort studies of ccTGA outcomes, it is clear that, on balance, the systemic RV in a ccTGA circulation provides a more durable alternative than either a RV-based, LV-based, or 2-ventricle univentricular circulation.…”
Section: Cctga and The Fate Of The Systemic Rvmentioning
confidence: 95%
“…The LVOTO and positional heart anomalies made it very difficult to construct the traditional atrial baffle of the Senning and Mustard procedures, so significant technical challenges would be encountered with biventricular repair. Early survival rates are good with physiological repair, but mid-and long-term outcomes were disappointing in some reported studies (2)(3)(4)(5). Fontan operation has the advantage of low operative risk and superior early surgical outcomes but carried with it the inherent features of chronic systemic venous hypertension, low cardiac output, and liver fibrosis, which could translate into poor quality of life and outcomes in the long term (6,7).…”
Section: Introductionmentioning
confidence: 99%